Implications of the Covid-19 Pandemi as Forcing Circumstances (Overmacht) in Credit Agreements - Arrosyiid, Haadi; Febriansyah, Ferry Irawan (NAJAHA, 2022)
This study discusses whether the Covid-19 pandemic can be classified as a force majeure (overmatch) in a credit agreement. This study uses a normative juridical method by conducting a literature study on legal materials obtained from laws, literature, and other books related to this writing. From the results of the research that has been done, the policies implemented during the Covid-19 pandemic could have gone better. This is marked by the continued decline in the community's economy, so the achievements in the agreements still need to be fulfilled. Many parties, one of which is a debtor in a credit agreement, have failed to pay by using force majeure (overmatch) to avoid responsibility for compensation. The Covid-19 pandemic can indeed be classified as a force majeure (overmacht) as long as the debtor can prove the reasons he stated to the creditor in several ways, namely 1) An unexpected event occurred, 2) An event that occurred beyond his control/fault, and 3) some events prevent the debtor from fulfilling his achievements.